The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.1038/srep36378
|View full text |Cite
|
Sign up to set email alerts
|

Impaired T Cell-dependent Humoral Immune Response Associated with Juvenile-onset Recurrent Respiratory Papillomatosis Progression

Abstract: Whether humoral immunity plays a role in HPV type 6 or 11 virus-mediated Juvenile-onset Recurrent Respiratory Papillomatosis (JORRP) remains unknown. In the present study, serum total IgG level in 44 JORRP patients was significantly decreased compared with that in 40 healthy controls. Moreover, expanded CD3−CD19+ B cells with down-regulation of CD23, CD40, HLA-DR and up-regulation of CD86 expression were found in the peripheral blood of JORRP patients. Flow cytometry analysis of B-cell compartment showed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 29 publications
(34 reference statements)
1
13
1
3
Order By: Relevance
“…In our previous studies, it has been revealed that children with JORRP exhibited a Th2-biased cytokine pro le [14]. Furthermore, we found that impaired T cell-dependent humoral immune response supported persistent HPV infection in JORRP [15]. These studies exposed the abnormal immune response of T cells to HPV in JORRP.…”
Section: Introductionsupporting
confidence: 60%
“…In our previous studies, it has been revealed that children with JORRP exhibited a Th2-biased cytokine pro le [14]. Furthermore, we found that impaired T cell-dependent humoral immune response supported persistent HPV infection in JORRP [15]. These studies exposed the abnormal immune response of T cells to HPV in JORRP.…”
Section: Introductionsupporting
confidence: 60%
“…Since introduction of HPV vaccination (Gardasil ® ) in Australia in 2007, there has been a marked reduction in clinic presentations for genital warts by Aboriginal and Torres Strait Islander Australians aged 21–30 years, 19 but not in older age groups. Surveillance studies continue to monitor new cases of HPV disease and associated types; however, HPV‐related disease remains a concern as does its role in humoral and innate immune impairment 3 . The question of whether HPV plays a role in the very high rates of respiratory infection with immune impairment 20 in Aboriginal infants remains incompletely addressed; however, our results suggest that vertical HPV transmission is an unlikely contributor.…”
Section: Discussionmentioning
confidence: 86%
“…In infants, the most commonly known manifestation of HPV is respiratory papillomatosis where stridor is often the presenting symptom. However, HPV infection is also associated with impaired humoral and innate immune responses that predispose the child to increased risk of infection 3 . Children may thus also present with recurrent pneumonia, bronchiectasis, and declining pulmonary status 2 .…”
Section: Introductionmentioning
confidence: 99%
“…T-cell surface marker staining and intracellular cytokine staining for flow cytometry analysis were performed as described previously. 23 , 24 In brief, freshly isolated PBMCs (Ficoll-Hypaque density gradients centrifugation) from fresh whole blood were stimulated with Phorbol-12-myristate-13-acetate (PMA, 50 ng/mL; Sigma-Aldrich) and ionomycin (1 μg/mL; Sangon Biotech) for 4 h. Cell surface staining was performed for 30 min at room temperature followed by fixation and permeabilization using an intracellular staining assay (BD Biosciences) according to the manufacturer's instructions. Cells were then stained with PE-anti-TNFα (Mouse IgG1, clone MAb11), APC-anti-IFNγ (Mouse IgG1, clone B27), or corresponding isotype control antibodies (all from BD Biosciences) at 4 °C for 30 min.…”
Section: Methodsmentioning
confidence: 99%